2015
DOI: 10.1007/s00049-015-0202-9
|View full text |Cite
|
Sign up to set email alerts
|

Soybean (Glycine max) plants genetically modified to express resistance to glyphosate: can they modify airborne signals in tritrophic interactions?

Abstract: Upon herbivory, plants activate complex biochemical pathways that result in an array of defense responses including the emission of a novel blend of volatile organic compounds (VOCs). These compounds mediate the recruitment of predators and parasitoids that exert biological control of the attacking herbivore. Genetic manipulation of a particular trait to improve agricultural plant varieties may affect other traits as a result of possible pleiotropy or insertional mutations, which in turn can affect the interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…larger fruit and seed sets) compared to their wild relatives 4 , 5 . It has been suggested that the over-expression of the epsps gene is responsible for these compensation effects on plant fitness, in view of the biotic and abiotic stressors that activate the shikimate pathway 5 , 15 . Further investigation to find out if this is the case for W cp4-epsps cotton is currently being developed under natural conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…larger fruit and seed sets) compared to their wild relatives 4 , 5 . It has been suggested that the over-expression of the epsps gene is responsible for these compensation effects on plant fitness, in view of the biotic and abiotic stressors that activate the shikimate pathway 5 , 15 . Further investigation to find out if this is the case for W cp4-epsps cotton is currently being developed under natural conditions.…”
Section: Discussionmentioning
confidence: 99%
“…cry and cp4-epsps ). Such differences have been associated with defence mechanisms and/or main metabolic pathways involved in plant growth, development, and reproduction, such as the shikimate or the octadecanoid pathways 15 , 16 . As a consequence, the quantity and quality of metabolic products are modified, compromising not only plant performance but also their interactions with insects, bacteria, and soil fungi 17 .…”
Section: Introductionmentioning
confidence: 99%
“…When infested by the leafminer species Phyllonorycter blancardella (Fabricius), the GM apple plants with a scab resistance gene emitted less ( E,E )-α-farnesene than did their conventional equivalents (Vogler et al, 2010). A transgenic soybean cultivar expressing a glyphosate-resistant gene released a few volatile compounds in a higher amount than did its conventional isoline when the plants were damaged by the soybean looper Chrysodeixis includes (Walker) or the velvetbean caterpillar Anticarsia gemmatalis Hübner (Strapasson et al, 2016a,b). As a result, the herbivore-damaged GM soybean plants were more attractive to the larval parasitoid Meteorus rubens (Nees) than the conventional isoline (Strapasson et al, 2016a).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the Bt maize line more likely releases several volatile compounds in a lower amount than does its non- Bt isoline due to deficiency of resources when the plants are induced by caterpillar regurgitant (Turlings et al, 2005). However, after genetic transformations, some inducible VOCs, such as terpenoids, have actually increased (Strapasson et al, 2016b). One possible explanation is that the newly biosynthesized protein (responsible for herbicide tolerance in this case) has affected or is involved in the plant hormone-mediated defensive pathway, which responds to produce some VOCs (Strapasson et al, 2016a).…”
Section: Discussionmentioning
confidence: 99%
“…While the first strategy would deprive the plant of part of its natural defenses and possibly result in the larger pesticide inputs, the second would not. Furthermore, genetic manipulation of plants can result in pleiotropic effects or mutations, affecting other plant traits, including those involved in defense (Strapasson et al, 2016). Contradictory as it may sound, South American Indians prefer to grow plants with larger amounts of cyanogenic glycosides (Wilson and Dufour, 2002).…”
Section: Plant Defense and Nutritional And Ecological Trade-offsmentioning
confidence: 99%